3D CMZ. I. Central Molecular Zone overview - Battersby, Cara; Walker, Daniel L.; Barnes, Ashley; Ginsburg, Adam; Lipman, Dani; Alboslani, Danya; Hatchfield, H Perry; Bally, John; Glover, Simon; Henshaw, Jonathan D.; Immer, Katharina; Klessen, Ralf S.; et al. (The astrophysical journal, 2025)
The Central Molecular Zone (CMZ) is the largest reservoir of dense molecular gas in the Galaxy and is heavily obscured in the optical and near-IR. We present an overview of the far-IR dust continuum, where the molecular clouds are revealed, provided by Herschel in the inner 40° (∣l∣ < 20°) of the Milky Way with a particular focus on the CMZ. We report a total dense gas (N(H2) > 1023 cm−2) CMZ mass of M⊙ and confirm that there is a highly asymmetric distribution of dense gas, with about 70%-75% at positive longitudes. We create and publicly release complete fore/background-subtracted column density and dust temperature maps in the inner 40° (∣l∣ < 20°) of the Galaxy. We find that the CMZ clearly stands out as a distinct structure, with an average mass per longitude that is at least 3× higher than the rest of the inner Galaxy contiguously from 18 > ℓ > −13. This CMZ extent is larger than previously assumed, but is consistent with constraints from velocity information. The inner Galaxy’s column density peaks towards the SgrB2 complex with a value of about 2 × 1024 cm−2, and typical CMZ molecular clouds are about N(H2) ∼ 1023 cm−2. Typical CMZ dust temperatures range from ∼12-35 K with relatively little variation. We identify a ridge of warm dust in the inner CMZ that potentially traces the base of the northern Galactic outflow seen with MEERKAT.